Emotions and Political Unrest - Passarelli, Francesco; Tabellini, Guido (Journal of Political Economy, 2017)
How does political unrest influence public policy? We assume that protests are an emotional reaction to unfair treatment. Individuals have a consistent view of fairness that internalizes government constraints. Individuals accept lower welfare if the government is more constrained. This resignation effect induces a benevolent government to delay unpleasant choices and accumulate public debt to mitigate social unrest. More radical and homogeneous groups are more prone to unrest and hence more influential. Even if the government is benevolent and all groups are identical in their propensity to riot, equilibrium policy can be distorted. The evidence is consistent with these implications.